Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jafc.2c05595
|View full text |Cite
|
Sign up to set email alerts
|

“Multiomics” Analyses Combined with Systems Pharmacology Reveal the Renoprotection of Mangiferin Monosodium Salt in Rats with Diabetic Nephropathy: Focus on Improvements in Renal Ferroptosis, Renal Inflammation, and Podocyte Insulin Resistance

Abstract: We explored the protection of mangiferin monosodium salt (MGM) on kidney injury in rats with streptozotocin (STZ)-induced diabetic nephropathy (DN) by “multiomics” analysis combined with systems pharmacology, with a specific focus on ferroptosis, inflammation, and podocyte insulin resistance (IR) signaling events in kidneys. MGM treatment afforded renoprotective effects on rats with STZ-induced DN by alleviating systemic IR-induced renal inflammation and podocyte IR. These mechanisms were correlated mainly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Another study revealed a Gpx4/ferroptosis suppressor protein 1/CoQ10 axis in podocytes, which meliorate renal ferroptosis. Then, utilizing systems pharmacology and ‘multi-omics’ analysis, researchers discovered the role of mangiferin monosodium salt (MGM), which inhibits lipid driver ACSL-4-mediated pro-ferroptosis synthesis in the kidney [ 60 ].…”
Section: Ferroptosis In Diabetic Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed a Gpx4/ferroptosis suppressor protein 1/CoQ10 axis in podocytes, which meliorate renal ferroptosis. Then, utilizing systems pharmacology and ‘multi-omics’ analysis, researchers discovered the role of mangiferin monosodium salt (MGM), which inhibits lipid driver ACSL-4-mediated pro-ferroptosis synthesis in the kidney [ 60 ].…”
Section: Ferroptosis In Diabetic Nephropathymentioning
confidence: 99%
“…In addition, some extracts from fruits and plants are useful. Mangiferin monosodium salt (MGM), a special component of mango, has also demonstrated a systemic protective role in DN by regulating lipid metabolism derange­ments and arachidonic acid (AA) metabolism [ 60 ]. A few plant extracts, like as Vitexin, are significant bioactive flavonoid monomers that demonstrate their anti-ferroptosis functions via stimulating GPX4 signaling [ 66 ].…”
Section: Ferroptosis In Diabetic Nephropathymentioning
confidence: 99%
“…99 Recent therapeutic interventions, such as mangiferin monosodium salt, Ginkgolide B, and germacrone, target ferroptosis suppression and are effective in managing diabetic nephropathy through minimizing oxidative stress. 98,100,101 There is currently a paucity of evidence linking ferroptosis directly to podocytes in LN patients; however, recent magnetic resonance analyses referencing three single-nucleotide polymorphisms (rs855791, rs1800562, and rs1799945, which were identified in an expansive genome-wide association study) have associated serum iron levels with susceptibility to SLE. 97 Podocyte ferroptosis might have significant implications for LN patients, whether directly or indirectly.…”
Section: Ferroptosismentioning
confidence: 99%
“…Compounds that inhibit ferroptosis, such as ferrostatin‐1, exhibit therapeutic potential by mitigating the expression of GPX4 in podocytes, resulting in a marked reduction of proteinuria and a decrease in podocyte mortality in focal segmental glomerulosclerosis patients 99 . Recent therapeutic interventions, such as mangiferin monosodium salt, Ginkgolide B, and germacrone, target ferroptosis suppression and are effective in managing diabetic nephropathy through minimizing oxidative stress 98,100,101 …”
Section: Pathophysiology Of Podocyte Injury and Death In Lnmentioning
confidence: 99%
“…These effects are mainly attributable to the inhibition of the MAPK/NF-κB pathway and activation of the phosphorylated insulin receptor substrate 1 (Tyr608)/phosphorylated PI3K/phosphorylated Akt pathway in the DN rat kidney. MGM ameliorated renal ferroptosis in STZ-induced DN rats by upregulating mevalonate (MVA)-mediated antioxidant capacity (Gpx4 and FSP1/CoQ10 axis) and attenuating ACSL4-mediated renal lipid driver production ( 212 ).…”
Section: Ferroptosis Inflammation and Diabetic Nephropathymentioning
confidence: 99%